2012
DOI: 10.1021/es300274t
|View full text |Cite
|
Sign up to set email alerts
|

Transitions from Functionalization to Fragmentation Reactions of Laboratory Secondary Organic Aerosol (SOA) Generated from the OH Oxidation of Alkane Precursors

Abstract: Functionalization (oxygen addition) and fragmentation (carbon loss) reactions governing secondary organic aerosol (SOA) formation from the OH oxidation of alkane precursors were studied in a flow reactor in the absence of NO(x). SOA precursors were n-decane (n-C10), n-pentadecane (n-C15), n-heptadecane (n-C17), tricyclo[5.2.1.0(2,6)]decane (JP-10), and vapors of diesel fuel and Southern Louisiana crude oil. Aerosol mass spectra were measured with a high-resolution time-of-flight aerosol mass spectrometer, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
249
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(292 citation statements)
references
References 56 publications
39
249
3
1
Order By: Relevance
“…Given the Van Krevelen diagram analysis described above in section 3.2.2, fragmentations reactions appear not to be the dominant oxidation pathway. This conclusion is consistent with the recent work of Lambe et al [2012] that showed that for larger alkanes, the onset of fragmentation occurs at an O : C of about 0.3, which is much higher than the O : C of HOA reported here (0.14). For functionalization reactions, based on the OM : OC ratio of 1.3 for HOA and an estimated OM : OC of 1.2 for an un-oxidized alkane chain, it is calculated that the increase in HOA mass due to oxidation is only 8%, which is smaller than the standard deviation (21%) of the data shown in Figure 8.…”
Section: The Quantitative Dependence Of Secondary Organicsupporting
confidence: 94%
“…Given the Van Krevelen diagram analysis described above in section 3.2.2, fragmentations reactions appear not to be the dominant oxidation pathway. This conclusion is consistent with the recent work of Lambe et al [2012] that showed that for larger alkanes, the onset of fragmentation occurs at an O : C of about 0.3, which is much higher than the O : C of HOA reported here (0.14). For functionalization reactions, based on the OM : OC ratio of 1.3 for HOA and an estimated OM : OC of 1.2 for an un-oxidized alkane chain, it is calculated that the increase in HOA mass due to oxidation is only 8%, which is smaller than the standard deviation (21%) of the data shown in Figure 8.…”
Section: The Quantitative Dependence Of Secondary Organicsupporting
confidence: 94%
“…At the extreme oxidant exposures used in the present study, fragmentation reactions (CÀ ÀC bond cleavage, Ng et al 2011a) may begin to form lower-volatility products, reducing the observed emission factors (Lambe et al 2012). The importance of fragmentation reactions may be lower for cyclic organics such as levoglucosan (for which CÀ ÀC bond cleavage does not split the molecule), which are contained in large amounts in wood-burning OM (Shafizadeh 1985;Rogge et al 1998;Simoneit et al 1999;Fine et al 2001;Graham et al 2002).…”
Section: Wood-stove Emission Factorsmentioning
confidence: 76%
“…The yields, composition, and properties of the SOA depend not only on alkane structure, however, but also on the extent of aging of the product mixture via OH radical oxidation and nonoxidative heterogeneous/multiphase reactions. Whereas recent studies have investigated the effects of aging on the yield, volatility, and oxidation state of SOA formed from alkanes in the presence (Bahreini et al 2012;Tkacik et al 2012) and absence Lambe et al 2012;Yee et al 2012) of NO x , to our knowledge only the studies by Yee et al (2012) and Craven et al (2012) of the reaction of n-dodecane in the absence of NO x has identified specific reaction products and mechanisms responsible for SOA aging. Here, we report the results of a study that employed particle mass spectrometry, TPTD, functional group analysis, elemental analysis, and measurements of SOA yields to investigate the chemistry of SOA formation from the reaction of OH radicals with n-pentadecane (the C 15 n-alkane IVOC) in the presence of NO x , and the mechanisms by which aging alters the molecular composition and volatility of the SOA.…”
Section: Introductionmentioning
confidence: 99%